2018
DOI: 10.1159/000495639
|View full text |Cite
|
Sign up to set email alerts
|

Hemodialysis or Peritoneal Dialysis, Which Is Better for Patients with Delayed Graft Function?

Abstract: Background/Aims: Hemodialysis (HD) or peritoneal dialysis (PD) is an important renal replacement method in patients with delayed graft function (DGF) after kidney transplantation; however, it is not clear which dialysis modality is superior. This study determined the impact of different dialysis modalities on patients with DGF. Methods: It was a single-center, retrospective and descriptive study. We performed 673 kidney transplants from donors after cardiac death (DCD) between January 2010 and December 2016 at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 19 publications
2
9
1
Order By: Relevance
“…Our peritonitis rate of 6.25% during DGF was much lower compared to some of the earlier studies reporting these outcomes. [19][20][21] These were comparable to the study by Yan et al 30 Contrary to the above-mentioned studies, our study did not find any case of wound infection or leakage in patients who underwent PD for DGF. One reason for the observed lower rate of complications could be a strict patient selection, as any patient with a potential breach in the peritoneal membrane was excluded.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Our peritonitis rate of 6.25% during DGF was much lower compared to some of the earlier studies reporting these outcomes. [19][20][21] These were comparable to the study by Yan et al 30 Contrary to the above-mentioned studies, our study did not find any case of wound infection or leakage in patients who underwent PD for DGF. One reason for the observed lower rate of complications could be a strict patient selection, as any patient with a potential breach in the peritoneal membrane was excluded.…”
Section: Discussionsupporting
confidence: 89%
“…37,38 All of these factors may contribute to a speedy recovery of graft function in PD patients. Similar to the two studies mentioned above from Thomson et al 29 and Yan et al, 30 we did not notice any significant difference in long-term graft survival or graft function at the time of last follow-up, indicating that the choice of modality at the time of DGF may not impact long-term outcomes. Rejection within first year and the presence of postsurgery complications were the only factors associated with a higher risk of DCGF.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The authors 5 found that the risk factors for peritonitis were more than 2 acute rejection episodes, previous history of peritonitis, and PD catheter exit site infections, technical issues during transplantation including accidental visceral injury or urinary leak, and primary renal allograft nonfunction. On the other hand, Andreetta et al 6 and Yan et al 7 reported a relatively low risk of peritonitis with performing PD posttransplantation. However, the current study by Gardezi et al 1 is somehow at odds with those previously published studies reporting a lower rate of peritonitis of 6.25% during DGF.…”
Section: See Clinical Research On Page XXXmentioning
confidence: 99%